PENGAWASAN LALU LINTAS DALAM MENGATASI KEMACETAN OLEH DINAS PERHUBUNGAN DI KOTA PEKANBARU TAHUN 2016 - Novrisaldi Nasution; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Town of Pekanbaru in this time represent as town which is flange to Townof metropolitandengan various accessing development and also facility whichprogressively expand. It is of course the mentioned will add the amount of residentresiding in in Town of Pekanbaru, as according to Vision Mission Town ofPekanbaru in this time [is] to